Taṭwīr al-Mawād at-Ta`līmiyyah Li Barāmij al-Lughah al-`Arabiyyah Li Aghrāḍ Khāṣṣah Bi Istikhdām Taqniyyah al-Wāqi` al-Mu`azzaz - Anis Azrina Anuar; Mohamed Abdul Rahman Ibrahim Youssef (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
Exploiting advanced technological tool is considered as one of the requirements for the field of language education in the 21st century. Sadly, the field of teaching Arabic for Specific Purposes (ASP) is still a little behind when it comes to integrating these new educational tools into the teaching and learning processes. This will consequently result in decreasing the students’ motivation, as teachers still apply traditional teaching and learning methods, with a basic use of technology. It is important to note that the students in this generation utilize technology in their daily life, thus integrating these technologies in learning Arabic for Specific Purposes will benefit them in numerous aspects. Consequently, this study suggests the importance of developing learning materials using augmented reality technology for ASP modules. This study will shed a light on the concept of development, learning materials, and augmented reality. Finally, it will discuss about possible ways to develop ASP modules using augmented reality technology. It is hoped that this study will lead to advancement of educational tools for the field of ASP in the future.